The Effect of Training, Compensation and Employee Engagement on Organizational Culture as Mediating Variables on The Performance of Integrated Islamic Elementary School Teachers Region of Gorontalo - Amna Raihan Mustafa; Mulyadi Mulyadi; Asep Saifudin; Deni Gustiawan (Green Publisher Indonesia, 2025)
This research aims to determine and analyze the influence of training, compensation, and employee engagement on the performance of integrated Islamic elementary school teachers in the Gorontalo region, with organizational culture as a mediating variable. This research includes quantitative research. The population in this study was all elementary school-level teachers who were members of the Gorontalo Region Indonesian Integrated Islamic School Network, totaling 172 people. The sample in this study was 120 people determined using the Slovin formula. This research uses a Structural Equation Model (SEM) approach with a measurement model using the LISREL 8.8 program. The research results show no significant influence between training and compensation on organizational culture and the performance of integrated Islamic elementary school teachers in the Gorontalo region, or whether it is mediated by organizational culture. The variable that significantly influences employee engagement on organizational culture and performance is mediated by organizational culture.